Commodification of knowledge in higher education: Where is the seat of Maqasid Al-Shari'ah and Islamisation? - Othman, Azam; Hussien, Suhailah; Md. Sidek, Suzana Suhailawaty; Faizuddin, Ahmad (IIUM Press, 2017)
The condition of knowledge in the globalization era can be easily commercialized with the support of advanced technology. The transformation of technology in the 21st century has changed the way learning is acquired and exploited. Globalization also has brought new challenges to higher education in terms of economy, politics, culture and technology. This scenario has expedited the process of adopting commodification of education. As a result, higher education institutions are becoming more like suppliers of the education market where students are primarily consumers. Educators and policy makers have drifted away from advocating integrated education as social good to produce good human beings (al-Insan al-Saleh). Some educational programs have been commercialized in pursuit of monetary gain for the survival of universities’s life span. Instead of preserving the noble maqasid of al-shari’ah and Islamisation, integration, and comprehensive excellence, universities have been pressured to generate income. This influences the quality of education and has jeopardized the noble mission and vision of the Universities, particularly the principles of maqasid al-Shari’ah and the Islamisation agenda in Islamic universities. Taking into account the dilemmas of these Islamic universities in balancing its Islamisation agenda with pressures of commodification of knowledge, this article argues that the concept of Islamization of knowledge can be preserved within the context of social welfare. From the Islamic perspective, the principles of maqasid al-shari’ah AZAM OTHMAN 224 (the purposes of Islamic Law) have significant impacts on social and cultural circumstances. It is also due to the fact that the concept of maqasid al-shari’ah include the preservation of five basic foundations, i.e. religion (din), life (nafs), mind (‘aql), offspring (nasb), and wealth (mal). Since universities, including Islamic universities do not have much choices, we argue that adopting the principles of maqasid al-shari’ah to commercialize educational programs is promising and can be made plausible.